Tổng hợp các dẫn xuất halogeno-indan mới - Phong Lan và cộng sự, Phạm Khánh (Vietnam Journal of Chemistry, 2014)
During the course of our work aiming at researching new compounds and showing a biological interest, we improved the pharmacomodulation of new cyclopenta[c]thiophene derivatives which have been characterized as potent cytotoxic derivatives. Within this framework, we wish to report herein the results concerning the synthesis of their isosters - the new halogeno-indane compounds, with the replacement of the thiophene ring by various substituted benzene ring (bromo and chlorobenzene).